RELEVANSI KURIKULUM DENGAN KEBUTUHAN KETERAMPILAN DI DUNIA KERJA PADA PROGRAM STUDI TEKNIK SIPIL BANGUNAN GEDUNG UNP (Studi kasus: PT. Waskita Karya) - Muhammad Kurniawan; Dr. Nurhasan Syah, M.Pd (Universitas Negeri Padang, 2019)
Abstract— This research aims to determine the relevance of the curriculum with the skills requirements at PT. Waskita Karya Indarung VI Project on the Civil Building Engineering Study Program (D3) UNP, and knew the opinions and skills are needed by PT. Waskita Karya is based on the curriculum taught, because it is ready to face the world of work. This research is descriptive research and the sample of this study used the Purposive Sampling method, with a sample of 11 employees of PT. Waskita Karya. The used instrument is a questionnaire that aims to measure skill needs variables with statement items as many as 154 items. The results of this study indicate that the curriculum of the Building Civil Engineering Program (D3) in 2017 has a connection and a closer relationship with the skills needed by PT. Waskita Karya Project Indarung VI. From this explenation be concluded that there is a relevance of the curriculum with skills needs in the world of work in the Building Civil Engineering Study Program (D3) of 82%. Keywords: Requirement of skills, Curriculum of Civil Engineering Building, PT. Waskita Karya.